Platinum(IV) Derivatives of [Pt(1S,2S-diaminocyclohexane)(5,6-dimethyl-1,10-phenanthroline)] with Diclofenac Ligands in the Axial Positions: A New Class of Potent Multi-action Agents Exhibiting Selectivity to Cancer Cells - Kostrhunova, Hana; McGhie, Brondwyn S; Markova, Lenka; Novakova, Olga; Kasparkova, Jana; Aldrich-Wright, Janice R; Brabec, Viktor (Journal of medicinal chemistry, 2023)
The platinum(II) complex [Pt(1S,2S-diaminocyclohexane)(5,6-dimethyl-1,10-phenanthroline)]2+ (PtII56MeSS, 1) exhibits high potency across numerous cancer cell lines acting by a multimodal mechanism. However, 1 also displays side toxicity and in vivo activity; all details of its mechanism of action are not entirely clear. Here, we describe the synthesis and biological properties of new platinum(IV) prodrugs that combine 1 with one or two axially coordinated molecules of diclofenac (DCF), a non-steroidal anti-inflammatory cancer-selective drug. The results suggest that these Pt(IV) complexes exhibit mechanisms of action typical for Pt(II) complex 1 and DCF, simultaneously. The presence of DCF ligand(s) in the Pt(IV) complexes promotes the antiproliferative activity and selectivity of 1 by inhibiting lactate transporters, resulting in blockage of the glycolytic process and impairment of mitochondrial potential. Additionally, the investigated Pt(IV) complexes selectively induce cell death in cancer cells, and the Pt(IV) complexes containing DCF ligands induce hallmarks of immunogenic cell death in cancer cells.
Keywords: diklofenak; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; platina; Diclofenac; Ligands; nádory; Platinum; Organoplatinum Compounds; nádorové buněčné linie; Prodrugs; protinádorové látky; organoplatinové sloučeniny; ligandy; Cell Line, Tumor; Neoplasms; prekurzory léčiv; Antineoplastic Agents